2020
DOI: 10.5851/kosfa.2020.e74
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gelatin Hydrolysates Addition on Technological Properties and Lipid Oxidation of Cooked Sausage

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article Title Effects of gelatin hydrolysates addition on technological properties and lipid oxidation of cooked sausage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…, 2018), but there were no differences between the sausages with 2.0 and 3.0% SPIH ( p > 0.05). Ham et al. (2020) also reported that the addition of 1% gelatin hydrolysate caused an decreasing trend in cooking loss of the meat batters.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…, 2018), but there were no differences between the sausages with 2.0 and 3.0% SPIH ( p > 0.05). Ham et al. (2020) also reported that the addition of 1% gelatin hydrolysate caused an decreasing trend in cooking loss of the meat batters.…”
Section: Resultsmentioning
confidence: 91%
“…When the addition of SPIH reached 3.0%, the cooking loss increased, which may be attributed to the fact that higher concentration of SPIH in sausages affected the formation of protein network and protein film, resulting in fat and water exudation (Ghribi et al, 2018), but there were no differences between the sausages with 2.0 and 3.0% SPIH (p > 0.05). Ham et al (2020) also reported that the addition of 1% gelatin hydrolysate caused an decreasing trend in cooking loss of the meat batters. Barbut (2007) noted that adding the whey protein hydrolysate helped to reduce cooking loss of frankfurter-type product below the level seen in the control.…”
Section: Cooking Lossmentioning
confidence: 91%
“…Gelatin is a potential derivative product of collagen protein and can be applied in various industries, both food and nonfood industries [6][7][8]. The use of gelatin in the processing of emulsion products such as surimi [9,10] and sausages has been widely practiced [11][12][13][14][15]. This study will try to observe the effect of adding snakehead fish gelatin to sausage-based beef cheek meat.…”
Section: Introductionmentioning
confidence: 99%
“…Sausage is a processed food that continues to innovate in its composition and formulation. The use of several emulsifiers, both based on polysaccharides [17] and protein [9,13,14], is still a suitable alternative for sausage products. The nature of the emulsion in sausages is two phases in the dough with polar and nonpolar charges which can affect each other if the intermediate binder works well and is well dispersed in the liquid and fat added to the dough.…”
Section: Introductionmentioning
confidence: 99%